The icing on the cake - Levine, Deborah A.; Riley, JillEllyn (Levine, Deborah A. Saturday cooking club, 2015)
Liza's thirteenth birthday is hijacked by her Nana Silver, who wants to throw her granddaughter a party more suited for a society page than the low-key celebration Liza wants. However, Liza's best friends Frankie and Lillian create a plan to save Liza.